Multimode Friedel oscillations in monolayer and bilayer graphene - Chiun-Yan Lin; Chih-Wei Chiu (Scientific Reports)
Abstract This study systematically explores the influence of charged impurities on static screening in monolayer graphene and extends the investigation to AA-stacked and AB-stacked bilayer graphene (BLG). Applying the random phase approximation (RPA), monolayer graphene displays unique beating Friedel oscillations (FOs) in inter-valley and intra-valley channels. Shifting to BLG, the study emphasizes layer-specific responses on each layer by considering self-consistent field interactions between layers. It also explores the derived multimode FOs, elucidating distinctions from monolayer behavior. In AA-stacked BLG, distinct metallic screening behaviors are revealed, uncovering unique oscillatory patterns in induced charge density, providing insights into static Coulomb scattering effects between two Dirac cones. The exploration extends to AB-stacked BLG, unveiling layer-specific responses of parabolic bands in multimode FOs with increasing Fermi energy. This comprehensive investigation, integrating RPA considerations, significantly advances our understanding of layer-dependent static screening in the broader context of FOs in graphene, providing valuable contributions to the field of condensed matter physics.